Kawin Hamil Perspektif Mazhab Fikih, Kompilasi Hukum Islam dan Maqāshid Syarī’ah (Sebuah Kajian Komprehensif) - Fathoni, Muhammad Nur; Angkasa, Nawa; Tarmizi, Tarmizi (Syakhsiyah Jurnal Hukum Keluarga Islam, 2023)
Marriage based on the provisions of Allah and His Messenger will make a happy household in this world and the hereafter based on sharia. The development of current trends in communication, information and technology can disrupt the noble value of marriage if it is misunderstood and misused. The real negative impact that occurs in society is the increasing number of women who become pregnant outside of marriage due to promiscuity. This study aims to examine the law of pregnant marriages in terms of three legal perspectives; Mazhab Fikih, Compilation of Islamic Law (KHI) and Maqāshid Shariā'h. This research is literature research with a literature approach. This type of research is library research with a document study approach where primary and secondary data are obtained from books, journals, books and references that discuss pregnant marriages. The results of this study found that the Ulama Mazhab Fikih discusses the act of pregnant marriage in Fikih and there is khilafiyyah related to the provisions and conditions for pre-marrying women who are pregnant outside of marriage and after marriage. The Compilation of Islamic Law (KHI) which regulates pregnant marriages in article 53 has fulfilled the five main objectives of sharia (adh-Dharūriyyah al-Khamsah); maintaining religion, soul, intellect, offspring/honor, and property after being reviewed with Maqāshid Sharī'ah.